Application of STAD Cooperative Learning Model with Authentic Assessment of Increasing Knowledge Competencies and Competencies of Social Attitudes of Students at SMPN 40 Makassar - Hasmawati Hasmawati; Fakhruddin Fakhruddin; Muhammad Arifai; Najmiah Najmiah; Nurjannah Nurjannah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
The national education exam above explains that Indonesia's implementation of education is directed at preparing quality human resources, namely obedience to religious teachings, healthy body and soul, knowledgeable, independent, creative, and responsible. This study aimed to obtain, analyze, interpret, and describe/describe the data regarding the level of knowledge competence and social attitude competence of class VIII students of SMPN 40 Makassar through the application of the STAD cooperative learning model with authentic assessment. The research design used was a quasi-experimental design with a nonequivalent control group design in which neither the experimental group nor the control group was chosen randomly. This study's results are the competence of knowledge through the application of conventional learning models for students of class VIIIISMP Negeri 40 Makassar in the excellent category with an average score of 75.6364. The level of knowledge competence through applying the STAD cooperative learning model with authentic assessment for class VIIISMP Negeri 40 Makassar students is in the excellent category, with an average score of 82.3030. The competency level of social attitudes through applying conventional learning models for class VIIISMP Negeri 40 Makassar students is in a suitable category, with an average score of 80.8083. The level of social competence through applying the standard cooperative learning model with authentic assessment for students of the 40 State Viiismp class in Makassar is in the outstanding category with an average of 90.7647. There is a significant effect of applying the standard cooperative learning model with an authentic assessment of students' knowledge competence in class VII SMP Negeri 40 Makassar. There is a significant effect of applying the standard cooperative learning model with an authentic assessment of the competence of students' social attitudes in class VII SMP Negeri 40 Makassar.